Chapter 8: Fostering project social sustainability through stakeholder inclusion - Di Maddaloni, Francesco; Davis, Kate (Edward Elgar Publishing, 2024)
In project-based organizations, it is essential to respect the needs and expectations of different stakeholders. Sustainability and social outcomes have gained increasing importance, reflecting the demand for positive results in economic, social, and environmental areas. These results determine the actual value an organization contributes to its stakeholders. Aligning with the United Nations’ Sustainable Development Goals, organizations should prioritize sustainable economic growth, infrastructure, reduced urban inequalities, and partnerships in society. Neglecting social sustainability can lead to inequalities and suffering within local communities, posing reputational risks, particularly in complex projects. This chapter emphasizes the significance of stakeholder inclusion in project decision-making for better social sustainability. Project organizations should adopt a strategic and systematic approach, actively involving and harmonizing the interests of all stakeholders to achieve organizational goals and contribute to a cohesive and sustainable world.
Keywords: Sustainability; Social sustainability; Stakeholder inclusion; Project organisations; Decision-making process; Inclusive governance